PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT PESONA PUTRA PERKASA DI PAMULANG - Juita Dwi Safitri; Agus Sudarsono (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of product and service quality on customer satisfaction at PT Pesona Putra Perkasa, both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used was incidental sampling, namely using a population of 8,018 customers samples of 99 respondents. The analytical methods used include instrument tests, with validity tests, reliability tests, classical assumption tests, with normality tests, multicollinearity tests, heteroscedasticity tests, quantitative tests with linear regression analysis tests, correlation coefficient analysis, coefficient of determination analysis, and Hypothesis Testing as a means of proving the hypothesis. This is proven by the results of the product quality hypothesis test, which obtained a tcount value of 14,656 > ttable 1,984 and was strengthened by the ρ value < Sig.0.05 or a significance value < 0.05 (0.000 < 0.05). (0.000 < 0.05). The research results of product and service quality partially have a positive and insignificant effect on customer satisfaction at PT Pesona Putra Perkasa as shown by the multiple linear regression equation Y = 1.054 + 0.631X1 + 0.361X2. This is proven by the results of simultaneous hypothesis testing obtained by the Fcount value (180.325 > Ftable 3.09) and reinforced by the significance value < 0.00 (0.000 < 0.05). shows that the correlation coefficient is at the level of 0.800 - 1.000, so the level of correlation between product and service quality variables and customer satisfaction is interpreted as very strong. The coefficient of determination value is 0.785 or 78.5% while the remaining 21.5% is influenced by other factors. Thus, H03 is rejected and Ha3 is accepted. This means that it is proven that there is a simultaneous insignificant influence between product quality (X1) service (X2) on customer satisfaction (Y)